2023
DOI: 10.1111/cote.12704
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the dyeing using natural indigo (Indigofera tinctoria): Toward an environmentally friendly garment

Abstract: Currently, the use of natural indigo dye has been treated as an alternative to overcome the environmental pollution caused by synthetic indigo. Irrespective of the indigo dye source, it must be reduced to its soluble form by using reducing agents in a suitable alkaline environment. Herein, bio‐sugars such as glucose or fructose were used for this purpose. The results revealed that when fructose was used instead of glucose, colour strength (K/S) values increased. In this work, cotton was cationised with water‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The results showed that the colour change was evident when there was a 2:8 (v/v) ratio of CUR and purple sweet potato anthocyanins, which could be used to detect the freshness of fish (Chen et al ., 2020). IND is one of the earlier natural pigments used and is commonly used in the food, pharmaceutical, printing, and dyeing industries (Silva et al ., 2023). Therefore, the mixed indicator of CUR and IND prepares the indicator membrane to improve the indication effect.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the colour change was evident when there was a 2:8 (v/v) ratio of CUR and purple sweet potato anthocyanins, which could be used to detect the freshness of fish (Chen et al ., 2020). IND is one of the earlier natural pigments used and is commonly used in the food, pharmaceutical, printing, and dyeing industries (Silva et al ., 2023). Therefore, the mixed indicator of CUR and IND prepares the indicator membrane to improve the indication effect.…”
Section: Introductionmentioning
confidence: 99%